Analisis Implementasi Standar Operasional Prosedur Pembersihan Kamar Tamu di Palm Homestay Kuta Lombok - Octaviani Gita Putri; Suryani Wardtul Jannah; Bartolomeus Herawan Mintardjo; Agus Gunawan; Dewi Hermawati Wahyuningsih; Aulia Firmansyah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Amidst increasing guest expectations for accommodation cleanliness and comfort, the implementation of standard operating procedures (SOPs) in housekeeping services has become a crucial aspect in the hospitality industry. Good guest room cleanliness not only enhances comfort but also strengthens an accommodation's image and reputation. One example of an accommodation that implements a room cleaning SOP is Palm Homestay Kuta Lombok. This study aims to analyze the implementation of the SOP for guest room cleaning at Palm Homestay Kuta Lombok, evaluate the extent to which the SOP is implemented, and identify problems encountered and possible solutions for improvement. The research method used in this study is a qualitative approach with data collection techniques through observation, interviews, and documentation. Observations were conducted directly in the field to assess how the room cleaning SOP is implemented, while interviews were conducted with housekeeping staff and management to obtain their perspectives on obstacles and solutions encountered in the cleaning process. The documentation collected includes written SOPs and supervisory notes conducted by management. Based on the research results, the implementation of the room cleaning SOP at Palm Homestay Kuta Lombok can be said to be running quite well. However, several obstacles remain, such as inappropriate placement of amenities, inconsistent dusting methods, and limited cleaning equipment. These obstacles can impact the quality of room cleaning and guest comfort. Although improvements have been made, such as regular supervision and more consistent use of cleaning equipment, employee training still needs to be maximized. As a solution, this study recommends optimizing the budget allocation for employee training, with the aim of improving staff skills and understanding of the implemented SOPs.